A Case Study Using 10Be-26Al Exposure Dating at the Xi'an AMS Center. Issue 1 (19th January 2016) - Zhang, Li; Wu, Zhenkun; Chang, Hong; Li, Ming; Dong, Guocheng; Fu, Yunchong; Zhao, Guoqing; Zhou, Weijian
ABSTRACT: Exposure age dating using in situ 10 Be and 26 Al is a very useful technique for dating fluvial terraces. This is especially true in semiarid regions where other methods suffer from a paucity of suitable dating materials. This article describes sample preparation procedures and analytical benchmarks established at the Xi'an Accelerator Mass Spectrometry (AMS) Center for the study of in situ 10 Be and 26 Al. Four intercomparison samples were analyzed in the study, using an improved sample preparation method. The exposure age results are shown to be in good agreement with published data, and demonstrate the reliability of the dating method. This article also presents new 10 Be and 26 Al results from quartz samples collected from a series of fluvial terraces from Guanshan River, along the Qilian Shan, northeastern Tibetan Plateau. The ages of three fluvial terraces from the Jinfosi site are shown to be (56.4±5.3) ka for T3, (10.7±1.0) ka for T2, and (7.2±1.0) ka for T1. The dating results are consistent with published data from the same region ( 10 Be, 14 C, and optically stimulated luminescence dating methods). A comparison of high-resolution climate records with age constraints for the terrace formation shows a close relationship between terrace formation and climate change.